Hubungan Kedisiplinan Belajar dengan Prestasi Belajar Siswa - Anggraini, Reka; Sukma, Dina (Lembaga Yasin AlSys, 2024)
A common issue often encountered in schools is the lack of student discipline in adhering to regulations. Student discipline in learning is observed through their obedience to rules related to teaching and learning activities, including school entry and exit times, compliance with dress codes, participation in school activities, and more. Discipline in learning can enhance student academic performance. Thus, students with disciplined attitudes are likely to improve their academic achievements. This research employs a descriptive correlational method. The study population consists of 278 students in grades X and XI at SMAN 2 Bayang, with a research sample of 164 students selected through stratified random sampling. The results show a moderate and significant positive relationship between learning discipline and academic performance. The study recommends that guidance counselors increase their attention to students by providing informational services, group guidance, and individual counseling.